Pengaruh Disipilin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Koperasi di Desa Penebel - I Putu Ade Tisarana; I Wayan Suwendra (Ekuitas: Jurnal Pendidikan Ekonomi, 2026)
This study aims to analyze the effect of work discipline and work motivation on employee performance in cooperatives located in Penebel Village, Tabanan Regency. This research employs a quantitative approach with a causal design. The population consists of 51 cooperative employees, and a saturated sampling technique is used, meaning all population members are included as the sample. Data were collected through questionnaires using a Likert scale, supported by observation and documentation. The data were analyzed using multiple linear regression, preceded by classical assumption tests including normality, multicollinearity, and heteroscedasticity. The results indicate that work discipline has a positive and significant effect on employee performance, with a t-value of 4.315 and a significance level of 0.000. Work motivation also has a positive and significant effect, with a t-value of 18.993 and a significance level of 0.000, and shows a more dominant influence compared to work discipline. Simultaneously, work discipline and work motivation have a significant effect on employee performance, as indicated by an F-value of 3296.496 with a significance level of 0.000.